Finance and the Business Cycle: International, Inter‐Industry Evidence - BRAUN, MATÍAS; LARRAIN, BORJA (Journal of Finance, 2005)
ABSTRACT By considering yearly production growth rates for several manufacturing industries in more than 100 countries during (roughly) the last 40 years, we show that industries that are more dependent on external finance are hit harder during recessions. The observed difference in the behavior of industries is larger when financial frictions are thought to be more prevalent, linking the result directly to the financial mechanism hypothesis. In particular, more dependent industries are more strongly affected in recessions when they are located in countries with poor financial contractibility, and when their assets are softer or less protective of financiers.